TANZANIA’S POST-INDEPENDENCE ANTI-CORRUPTION EFFORTS: EXAMINING THE PREVENTION AND COMBATTING OF CORRUPTION BUREAU’S (PCCB) ROLE DURING MAGUFULI’S REGIME - Lukiko, Lukiko Vedastus; Kilonzo, Claudi; Kimela, Hasani (Journal of Anti-Corruption Law, 2023)
During the five years of John Magufuli’s presidency, Tanzania’s anti-corruption efforts yielded significant improvements. This improved performance was associated mainly with the President’s personal anti-corruption stance. Institutions entrusted with fighting corruption, particularly the Prevention and Combating of Corruption Bureau (PCCB), appear to be performing their functions based on the attitude of the incumbent President towards the problem. This creates a risk of personalising anti-corruption instead of institutionalising it. Unfortunately, President Magufuli passed away in March 2021 and the sustainability of his anti-corruption approach is now in question. This article assesses Tanzania’s post-independence efforts to fighting corruption, and specifically examines the role of the PCCB during the reign of President Magufuli. We argue that during Magufuli’s presidency, the anti-corruption approach in the country has been top-down instead of bottom-up. Decisions and directives to investigate and prosecute corruption have emanated from the President and other members of the Executive directed towards the PCCB, which is the primary organ in fighting corruption. The article proposes: the introduction of a constitutional anchor in the establishment and mandate of the PCCB and its staff; the abolition of the Director of Public Prosecutions (DPP) fiat in order to allow the PCCB to prosecute corruption offences without having to obtain consent of the DPP; and adopting various strategies to enlist public support in fighting this vice.